Life in the hothouse : how a living planet survives climate change - Lenart, Melanie, 1961- (Book collections on Project MUSE., 2010)
Why does the planet's warming produce stronger hurricanes, rising seas, and larger floods? The Earth is just doing what comes naturally. Just as humans produce sweat to cool off on a hot day, the planet produces hurricanes, floods, wetlands, and forests to cool itself off. This book incorporates the author's extensive knowledge of climate science, including the latest research in climate change, and the most current scientific theories, including Gaia theory, which holds that the Earth has some degree of climate control "built in." As the author points out, scientists have been documenting stronger hurricanes and larger floods for many years. There is a good reason for this, she notes. Hurricanes help cool the ocean surface and clear the air of carbon dioxide, the main greenhouse gas responsible for global warming. From the perspective of Gaia theory, these responses are helping to slow the ongoing global warming, and there is hope, she writes. If we help sustain Earth's natural defense systems, including wetlands and forests, perhaps Mother Earth will no longer need to rely as much on the cooling effects of what we call "natural disasters", many of which carry a human fingerprint. At a minimum, she argues, these systems can help us survive the heat.